A new species of Nemoura (Plecoptera: Nemouridae) from Central Italy - Fochetti, Romolo; Vinçon, Gilles (Zootaxa, 2009)
A new species of the genus Nemoura from Central Italy is described: Nemoura sabina sp. n. It belongs to the Nemoura flexuosa-marginata species group and had previously been confused with N. flexuosa. Its relationship to other species is discussed.